Expansion of Calanthe to include the species of Cephalantheropsis, Gastrorchis and Phaius (Collabieae; Orchidaceae) - Chase, Mark W.; Christenhusz, Maarten J. M.; Schuiteman, André (Phytotaxa, 2020)
To address the polyphyly of Phaius and Calanthe in recent molecular studies, we recommend the merger of these genera along with Cephalantheropsis and Gastrorchis, which are embedded among the first two genera. Some authors have instead proposed to segregate new genera from both Phaius and Calanthe, but this results in generic concepts for which there are no reasonable morphological differences. It is in the interest of nomenclatural stability to combine these genera, so we here make the necessary combinations and provide new names to enable users to employ this broadened generic concept of Calanthe.